KARAKTERISTIK DAN BAHAN PENYUSUN SARANG MEGAPODA ARFAK (AEPYPODIUS ARFAKIANUS) DI KAWASAN CAGAR ALAM PEGUNUNGAN ARFAK - Karim, Ikram; Sonbait, Lukas Y.; Pattiselanno, Freddy (Fakultas Peternakan Universitas Papua, 2018)
This study aimed to determine the characteristics of the nesting ground of Wattled Brushturkey (Aepypodius arfakianus), in Sigim village surrounding the Arfak Mountain Nature Reserve. The method used is descriptive method with survey and observation. Composition and characteristics of the nesting ground was analysed through observation and measurement of the studied variables. All the observation results obtained in this study were analysed using descriptive statistics. The results showed that nesting composition was consisted of 65% leaves, 31% twigs, 3,2% soil and 1% of small stones. The average height of the nests was 0,64 m and 1,80 m in diameter.